Innovation in MSME Digital Promotion Strategies as a Catalyst for Enhancing Tourist Visits in the Digital Economy Era - Krisnahadi, Tama; Octavia, Yusi Faizatul (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2025)
Micro, Small, and Medium Enterprises (MSMEs) play a crucial role in strengthening local economies and supporting the development of sustainable tourism. This study aims to analyze the forms and effects of MSME digital promotion strategy innovations on the increase of tourist visits in the digital economy era. The research employed a mixed method approach with a sequential explanatory design. The findings indicate that MSME digital promotion strategies have a positive and significant effect on tourist visits, as reflected in the regression equation Y = 23.744 + 0.339X, with a significance value of 0.018 (< 0.05). The most effective forms of digital promotion innovation include visual storytelling content and collaboration among tourism stakeholders through the use of social media platforms. The main supporting factors consist of human resource capabilities, product quality, tourist experience, and government support. The study concludes that digital promotion innovation plays a vital role in enhancing MSME competitiveness and stimulating local economic growth.